Bullying, cyberbullying e timidez como produtores de exclusão social, à luz da teoria histórico-cultural - Neves, Francisco Fabiano (Universidade Federal de São Carlos, 2024)
Social relations and culture are the bases for the development of higher psychic functions, which are unique to human beings. In this sense, the university is one of the social spaces that has the role of providing knowledge to the people who integrate and attend it, contributing to the development of these functions. In this research, which received financial support from the Coordination for the Improvement of Higher Education Personnel - Brazil - CAPES, we used the assumptions of the Historical-Cultural Theory. The objectives were to identify and analyze the influences of social relationships on the personality of shy people and how bullying and cyberbullying affect the daily lives of these people at university. Our hypothesis is that bullying, cyberbullying and shyness can be used as a means of excluding people from various spaces at university. Being in a capitalist society, the university can reproduce unequal and violent relations stemming from this economic model. The methodology used the genetic method, the principle of which is to go to the root of the object of study in order to explain it in objective reality. The instruments used were 32 questionnaires distributed to students on two undergraduate courses, a degree in Pedagogy and a degree in Physical Education. From the answers to the questionnaires, 13 participants were selected who considered themselves to be shy and who had suffered some form of bullying or cyberbullying. Of those selected, five agreed to take part in the interviews. The results of the questionnaires show that the students are afraid of social evaluation in most social relationships. In the interviews, reports of bullying involved racism, ageism, social exclusion because of gender and jokes containing prejudice. Reports of cyberbullying include gestures, jokes, harassment and intimidation in remote classes, which has led to isolation and avoidance of cameras depending on the social context, as well as social exclusion when returning to face-to-face teaching. In order to analyze the results, we drew up six guidelines for analysis: 1) Use of cameras during remote classes; 2) Return to face-to-face teaching; 3) Cases of bullying and cyberbullying; 4) Seeking help in cases of bullying and cyberbullying; 5) Personal and undergraduate learning; and 6) Capitalism and its interference in the socio-cultural environment. Thus, bullying and cyberbullying can be considered means of violence in capitalist society, used to maintain the privileges of certain social classes, since violence and social exclusion are ways of removing people from spaces to which they are entitled. The mediation needed in these cases must prevent and combat the conflicts and aggression that arise from bullying and cyberbullying. Higher education cannot shy away from this social problem. Transforming these issues involves the praxis of teachers, students and the engagement of collectives.
Bullying, cyberbullying and shyness as producers of social exclusion, in the light of cultural-historical theory
Keywords: Bullying; Cyberbullying; Shyness; University; Timidez; Universidade; CIENCIAS HUMANAS::EDUCACAO